Degradation of structural aircraft coatings in cyclic salt spray testing, outdoor exposure, and in-service environments - Cornet, A.J.; Homborg, A.M.; Hoen - Velterop, L. 't; Mol, J.M.C. (Springer, 2026)
Developing accelerated exposure tests that accurately predict the in-service performance of structural aircraft coatings remains challenging, largely due to the complexity of simulating real-world environmental conditions without altering key degradation mechanisms. This study evaluated four different coating systems under various accelerated exposure tests and compared their degradation behavior to in-service performance. Coating degradation was characterized using electrochemical impedance spectroscopy, scanning electron microscopy, and attenuated total reflectance Fourier transform infrared spectroscopy. Under in-service conditions, failure was primarily driven by the leaching of corrosion inhibitors, while the polymer matrix degraded predominantly through hydrolysis and thermo-oxidation. In contrast, during outdoor- or cyclic salt spray exposure, inhibitor leaching remained a key contributor to coating degradation although polymer degradation was mainly caused by ultraviolet radiation or hydrolysis. These findings emphasize the challenge of replicating real-world degradation in laboratory settings. Additionally, anodized oxide layers containing polymers within their pores played a critical role in maintaining protection during early coating failure. Chromate-based systems restored barrier properties, likely through chromate adsorption on hydrolyzed products within the oxide pores. In comparison, praseodymium-based systems failed to restore protection, while lithium-based systems sustained protection through an intact polymer.